2013
DOI: 10.1155/2013/895259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Cytogenetic, and Biochemical Analyses of a Family with a t(3;13)(q26.2;p11.2): Further Delineation of 3q Duplication Syndrome

Abstract: Chromosomal abnormalities that result in genomic imbalances are a major cause of congenital and developmental anomalies. Partial duplication of chromosome 3q syndrome is a well-described condition, and the phenotypic manifestations include a characteristic facies, microcephaly, hirsutism, synophrys, broad nasal bridge, congenital heart disease, genitourinary disorders, and mental retardation. Approximately 60%–75% of cases are derived from a balanced translocation. We describe a family with a pure typical part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Although, as outlined by Abreu‐González et al , the clinical manifestation appears to be dominated by the dup(3q) phenotype, these authors reviewed the findings from patients with pure dup(3q) only. Together with the data from our study, there are now at least 31 patients (25 unrelated cases) with a pure dup(3q) reported in the literature ( , , , this study). As correctly countered by Meins et al , a patient reported by Rosenfeld et al showed trisomy 3q21‐q26 but also monosomy for 3q27‐q29 and had to be excluded.…”
Section: Phenotypic Features Of Patients With ‘Pure’ Duplication 3qmentioning
confidence: 99%
See 4 more Smart Citations
“…Although, as outlined by Abreu‐González et al , the clinical manifestation appears to be dominated by the dup(3q) phenotype, these authors reviewed the findings from patients with pure dup(3q) only. Together with the data from our study, there are now at least 31 patients (25 unrelated cases) with a pure dup(3q) reported in the literature ( , , , this study). As correctly countered by Meins et al , a patient reported by Rosenfeld et al showed trisomy 3q21‐q26 but also monosomy for 3q27‐q29 and had to be excluded.…”
Section: Phenotypic Features Of Patients With ‘Pure’ Duplication 3qmentioning
confidence: 99%
“…There is a wide variability of dup(3q) syndrome, even within patients of the same family . According to the extent of the duplication and the clinical variability, the dup(3q) syndrome is suggested a contiguous gene syndrome, caused by more than one gene located in the critical region .…”
Section: Phenotypic Features Of Patients With ‘Pure’ Duplication 3qmentioning
confidence: 99%
See 3 more Smart Citations